2013
DOI: 10.1037/a0028497
|View full text |Cite
|
Sign up to set email alerts
|

Eye of the beholder: Effects of perspective and sexual objectification on harassment judgments.

Abstract: Social Analytic Jurisprudence instructs researchers to study the reciprocal relations between law and peoples' lives by developing empirical descriptions of legal assumptions about human behavior. The present work introduced a new experimental paradigm to test some of those assumptions by studying the impact of sexual objectification in a simulated job interview on performance, sexual harassment judgments, and emotions for women who experienced (akin to complainants), observed (akin to coworkers or witnesses),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 70 publications
8
61
0
Order By: Relevance
“…The male research assistant served as an interviewer, asking the participant to take a seat approximately 2 ft away. The interview consisted of 10 open‐ended questions assessing the participant's previous experience, skills, and interests in secretarial or creative tasks (modified from Gervais et al., and Wiener et al., ). Predictor participants were asked to read a transcript that explained that a male research assistant conducted an interview with a female student to decide whether the female student would complete a boring task, sorting 200 research articles into folders by topic, or an interesting task, creating a colorful poster to display the lab's recent research findings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The male research assistant served as an interviewer, asking the participant to take a seat approximately 2 ft away. The interview consisted of 10 open‐ended questions assessing the participant's previous experience, skills, and interests in secretarial or creative tasks (modified from Gervais et al., and Wiener et al., ). Predictor participants were asked to read a transcript that explained that a male research assistant conducted an interview with a female student to decide whether the female student would complete a boring task, sorting 200 research articles into folders by topic, or an interesting task, creating a colorful poster to display the lab's recent research findings.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Wiener et al. () found that women who anticipated an objectification experience in a work setting were more likely to report that it would be sexually harassing than women who actually experienced objectification in a work setting. One possibility is that predictors anticipate that women will feel worse following sexual objectification than women who experience objectification actually feel as a result of affective forecasting.…”
Section: Sexual Objectification As Sexual Harassmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable exception is the recent work by Wiener et al 2013). They randomly assigned male and female participants to experience either no objectifying gaze or a brief series of objectifying gazes from a confederate of the opposite sex during a brief interview.…”
Section: Participants As Objectifiersmentioning
confidence: 99%
“…Gervais, Wiener, and their colleagues Wiener et al 2013) have done this with their use of an objectifying gaze at a person's chest for various lengths of time during a face-to-face interview. While the person may have felt objectified, it may have been unclear as to whether that was the objectifier's intention.…”
Section: The Social Dynamics Of Objectification In Contextmentioning
confidence: 99%